Recent Developments in Photoalignment Technology:Alignment Properties of a Thiophene Based Bis-hydrazone Derivative - M. M., Yusoff; Hegde, Gurumurthy; Abhishek, K. Srivastava; A.V., Adhikari; K., Vishnumurthy; V.G., Chigrinov; H.S, Kwok (2012)
Liquid crystal photoalignment using commercially available azo dye CD-1 is reviewed. Proposed dye shows excellent alignment properties which is highly promisable for future applications. This photoalignment is based on rotational diffusion in a potential created by the light field as well as intermolecular forces. It will be shown that this photo-aligning dye shows strong anchoring energy of the LC cell and also having high thermal and ultraviolet (UV) stability. The application of liquid crystal displays using this dye is also discussed.